The Effect of Pecha Kucha Presentation in EFL Speaking Class - M. Fadhly Farhy Abbas; Shintia Dwi Putri; Marwa Marwa; Herdi Herdi (Universitas Lancang Kuning, 2017)
This study aimed at finding the significant differences in achievement between the students who are taught speaking by using the Pecha Kucha and those who are taught by using the Picture Series. This study was an experimental research which employed a quasi experimental design of two classes: one as the experimental A group taught using Pecha Kucha, and the other was the experiment B group taught using the Picture Series. Each class had 21 and 20 students. So the total number in the sample were 41 students in second semesters of English Education Department Faculty of Teacher Training and Education Lancang Kuning University. The instruments was a speaking test. The data from tests were analyzed by using the Statistical Package for the Social Sciences (SPSS). The result shows that Asym. Sig. (2-tailed)> Significant level that is 0.314 > 0,05, so Ho is accepted in which the students who were taught speaking through Pecha Kucha achieved a similar performance with the students who were taught speaking through Picture Series. This means that there is no significance difference in achievement between the students in both groups. Furthermore, the students were seen to be more active and creative in expressing their ideas.